plzz help me !
it's urgent
Attachments:
![](https://hi-static.z-dn.net/files/d6d/30960b41c9b08dc1e16b4a436c1ee17c.jpg)
Answers
Answered by
1
h Hf dfhnhhdhj is as take
Answered by
1
Step-by-step explanation:
==> [(-3 ) × 4/9 × (-27/2 ) ( XYZ × X^2 Z × XYZ^2 )
==> 18X^2 Y^3 Z^3
LHS,
( -3XYZ ) × ( 4/9 X^2 Y ) ( -27/2 XYZ^2 )
[(-3) × 2 × 3 × (-X) × [4/9 × (z)² (-1)]
[(-27/2) × 2 × (3)² × (-1)]
18×4/9 × 4 × (-1) × (-27/2) × X × 9 × (-1)
-7776.
RHS,
= 18 X^4 Y^3 Z^3
18 × (2)^4 × (3)^3 × (-1)^3
18 × 16 × 27 × (-1)
-7776
*LHS* = *RHS*
Similar questions
Physics,
8 months ago
Hindi,
8 months ago
Social Sciences,
8 months ago
English,
1 year ago
Science,
1 year ago
Science,
1 year ago
India Languages,
1 year ago